Student Entrepreneurship Development: A Case Study of Ganesha Entrepreneur Laboratory at STIE Ganesha - Ekky Noviar (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
This study aims to evaluate the student entrepreneurship development program organized by Ganesha Laboratorium Entrepreneur STIE Ganesha, focusing on the benefits, challenges, and need-based development strategies of private higher education institutions. This study is original and uses the CIPP (Context, Input, Process, Product) model evaluative approach with qualitative methods. Data were collected through a survey of 80 student respondents and supported by in-depth interviews and program documentation. Based on data from 80 respondents, the program succeeded in increasing motivation and entrepreneurial mindset (61.25%), increasing knowledge and skills (17.50%) and shaping creativity and innovation (11.25%). On the other hand, the main challenges include limited access to capital (43.75%), markets (32.5%), and weak post-program mentoring (1.25%). The findings suggest the need for sustainable strategies such as the integration of technopreneurship in the curriculum, the establishment of an entrepreneurship endowment fund, and the strengthening of campus business incubation. The implications of this study provide a practical contribution to the development of contextualized entrepreneurship models in private universities as well as supporting national policies in increasing the ratio of young entrepreneurs in Indonesia.